The use of infusion paracetamol in the multimodal management of post myomectomy pain: A randomised control study - Okojie NQ (Ibom Medical Journal, 2021)
Objective: The study evaluated the use of infusion paracetamol in the multimodal management of post myomectomy pain and its analgesic sparing effects while comparing the side effect profile. Methods: Sixty-two ASA I and II patients undergoing myomectomy under subarachnoid block were randomized into two groups which were either given infusion Paracetamol (perfalgan, Bristol-Myers Squibb) 100ml and rectal diclofenac (Voltaren, Novartis ), or infusion normal saline 100ml and rectal diclofenac (voltaren, Novartis) after the last skin stitch. Pain was assessed using NRS (Numerical rating scale). Patients were assessed for the presence of motor or sensory complications, rectal bleeding or gastrointestinal discomfort, postoperative nausea and vomiting and sedation. The presence of other side effects was noted. Patients’ satisfaction with pain relief using the 5-point Likert scale was also evaluated. Results: Time to first analgesic request was longer in the paracetamol/diclofenac group compared to the saline/diclofenac group. The time from intrathecal injection of bupivacaine and pethidine to first request for analgesia was 319.12±9.5 minutes in the paracetamol group as against 213.29±9.5 in the saline group. The mean pain scores at 2nd and 5th hour and at the time of first analgesic request were lower in patients in group P compared to the patients in the saline group. (4.83±1.6 vs 5.93±1.4) (P=0.012-test. Total analgesic consumption was more in the saline group. Conclusion: Infusion paracetamol provides additional analgesia in the management of post myomectomy pain.